Pengembangan Nilai-Nilai Lokal Filosofis, Edukasi dan Moral Orang Walak di Papua Pegunungan - Mikaus Gombo (Journal on Education, 2024)
This study aims to explore and describe local wisdom and local genius that encompass philosophical values within the culture of the traditional Walak community. The Walak community is part of the Balim people residing in the northern part of the Balim Valley, Papua. The research employs a qualitative method with a field study approach, involving interviews with several key informants.The findings reveal that the Walak community possesses various forms of local wisdom, such as philosophical phrases, educational and moral teachings, and sentences containing philosophical metaphors. This study recommends further development in education, particularly in the fields of educational philosophy and psychology based on local wisdom or ethno-education in Papua. Such education aims to reconstruct or reorganize life experiences, provide meaning, and guide individuals toward a better and more harmonious life.